Manufacturing method for high-strength parts with excellent resistance to hydrogen embrittlement

JP7644065B2Active Publication Date: 2025-03-11MITSUCHI CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022165794
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-14
Publication Date
2025-03-11
Estimated Expiration
2042-10-14

AI Technical Summary

Benefits of technology

【0010】 上記の製造方法では、上記した成分組成を有する金属粉末を用いて、三次元積層造形法により積層造形体を造形する。この製造方法では、エネルギー密度が60J/mm3以上であるレーザまたは電子ビームにより、当該金属粉末が完全に溶融されながら積層されることで、造形体の体積密度を99.9%以上とすることができる。この積層造形体は、造形時に内部残存する気孔や結晶粒界に生じるマイクロクラックが極めて少ないレベルに低減されているため、当該積層造形体を仕上げ加工することにより、高い強度を有するとともに耐水素脆性に優れた高強度部品を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644065000004
    Figure 0007644065000004
  • Figure 0007644065000005
    Figure 0007644065000005
  • Figure 0007644065000006
    Figure 0007644065000006
Patent Text Reader

Abstract

To provide a technique of producing a high-strength component with high strength and superior hydrogen brittleness resistance, using the three-dimensional additive manufacturing process.SOLUTION: A method for producing a high-strength component with superior hydrogen brittleness resistance includes the steps of: employs metal powder that contains, in wt.%, C: 0.010% or more and 0.025% or less, Si: 0.15% or less, Mn: 0.15% or less, P: 0.01% or less, S: 0.01% or less, Ni: 24% or more and 27% or less, Cr: 13.5% or more and 16% or less, Mo: 1% or more and 1.5% or less, V: 0.1% or more and 0.5% or less, Al: 0.35% or less, Ti: 1.90% or more and 2.35% or less, and B: 0.0006% or more and 0.0020% or less, to form an additive molded body with its volume density of 99.9% or more, by a three-dimensional additive manufacturing technique using laser or electron beams with an energy density of 60 J / mm3 or more; and subjecting the additive molded body to a finishing process, thereby producing a high-strength component.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The technology disclosed in this specification relates to a method for manufacturing a high-strength part, and more particularly, to a method for manufacturing a high-strength part having excellent resistance to hydrogen embrittlement. [Background technology]

[0002] Systems that use fuel cells and other devices that use hydrogen as an energy medium are being developed as the next-generation energy infrastructure. The hydrogen piping parts used in these systems, especially the piping joints, are exposed to high pressure or liquefied hydrogen, so they are required to be made of high strength steel and to be resistant to "hydrogen embrittlement of metals," a phenomenon unique to hydrogen.

[0003] Non-Patent Document 1 describes that steel materials containing components that allow a stable austenite structure are suitable, and as a component index, a nickel equivalent of 28.5 or more is a guideline for material selection and material development. Among existing steel materials that satisfy this component index, SUH660 specified in JIS G4311 is a steel material that has a high nickel equivalent and high strength, and the use of SUH660 for hydrogen piping parts, especially high-pressure piping joints (connectors), is being considered.

[0004] However, when such parts are manufactured, for example, by cutting the entire melted material, the poor machinability of the components that increase the nickel equivalent (Ni, Cr, etc.) significantly reduces the processing efficiency, and also leads to a deterioration in the quality of the cutting shape and surface roughness. In addition, a method of manufacturing a net-shape blank by forging is also considered for the purpose of reducing the cutting allowance, but since the above components are significantly hardened during forging, it is difficult to manufacture parts with shapes with large steps. Furthermore, the accuracy of cutting with a large cutting allowance and forging with large processing deformation is highly dependent on the skills of the worker, and therefore production efficiency and quality are likely to vary.

[0005] Meanwhile, as disclosed in Non-Patent Document 2, a technology has been developed recently for manufacturing objects of various shapes using various metal powders by metal three-dimensional additive manufacturing. This makes it possible to manufacture objects of relatively complex shapes, and allows the object to be designed in a shape close to the final finish shape, reducing the cutting allowance, thereby increasing the degree of design freedom. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Akira Saito, Toshio Tezuka, Yoshiaki Aikawa, Kazunori Kawamata, "Research and Development on Technical Standards for Hydrogen Infrastructure (Expansion of Steel Types)", 2019 [Non-Patent Document 2] Yuichiro Koizumi, Akihiko Chiba, Naoyuki Nomura, Takayoshi Nakano, "Fundamentals of 3D Additive Manufacturing Technology for Metallic Materials", 2017 Summary of the Invention [Problem to be solved by the invention]

[0007] Recently, the development of technology for manufacturing high-strength parts such as hydrogen piping parts using three-dimensional additive manufacturing has been progressing. However, depending on the components of the metal powder, microcracks (hereinafter referred to as microcracks) that occur in pores and grain boundaries remaining inside during molding are likely to occur, and compared with conventional steel materials (e.g., molten bar materials) containing the same components, the strength and hydrogen embrittlement resistance have not yet reached the required level. That is, there is a problem that molding defects cannot be sufficiently reduced regardless of how the irradiation conditions of the laser, etc. are changed due to factors on the material components. In particular, although the widely used SUH660 is used in molten bar materials as a material that is resistant to hydrogen embrittlement and has high strength to manufacture high-strength parts, the above-mentioned microcracks occur significantly in three-dimensional additive manufacturing bodies. In this specification, a technology is provided for manufacturing high-strength parts that have high strength and excellent hydrogen embrittlement resistance by three-dimensional additive manufacturing using metal powder having such a component composition. [Means for solving the problem]

[0008] The present inventors have intensively studied additive manufacturing objects manufactured by three-dimensional additive manufacturing, and as a result, have found that when a molten layer solidifies and when a layer laminated below the molten layer is reheated by the molten layer, liquation cracking or ductility dip cracking, i.e., microcracks occur along the grain boundaries due to the segregation of specific components at the grain boundaries. Then, after much trial and error, they have found that by using a metal powder whose composition is adjusted to a specific value within the range of the steel standard specified in JIS G4311, it is possible to impart high strength and excellent hydrogen embrittlement resistance to the additive manufacturing object.

[0009] The present specification discloses a method for producing a high-strength part having excellent hydrogen embrittlement resistance, which uses a metal powder having a component composition containing, by weight, C: 0.010% or more and 0.025% or less, Si: 0.15% or less, Mn: 0.15% or less, P: 0.01% or less, S: 0.01% or less, Ni: 24% or more and 27% or less, Cr: 13.5% or more and 16% or less, Mo: 1% or more and 1.5% or less, V: 0.1% or more and 0.5% or less, Al: 0.35% or less, Ti: 1.90% or more and 2.35% or less, B: 0.0006% or more and 0.0020% or less, with the balance being Fe and unavoidable impurities, and has an energy density of 60 J / mm 3 The method includes a step of manufacturing an additive manufacturing object having a volume density of 99.9% or more by the above-mentioned three-dimensional additive manufacturing method using a laser or electron beam, and a step of manufacturing a high-strength part by finishing the additive manufacturing object.

[0010] In the above manufacturing method, a metal powder having the above-mentioned component composition is used to manufacture an additive manufacturing body by a three-dimensional additive manufacturing method. 3By laminating the metal powder while completely melting it with the above-mentioned laser or electron beam, it is possible to achieve a volume density of the molded body of 99.9% or more. Since this additively molded body has extremely few pores remaining inside during molding and microcracks that occur at crystal grain boundaries, it is possible to obtain high-strength parts that have high strength and excellent resistance to hydrogen embrittlement by finish-processing the additively molded body. [Brief description of the drawings]

[0011] [Figure 1] FIG. [Diagram 2] FIG. [Diagram 3] FIG. [Figure 4] FIG. [Diagram 5] FIG. [Figure 6] FIG. [Figure 7] A figure showing multiple additively molded bodies 10 molded on a mold plate 50. [Figure 8] FIG. [Figure 9] Graph showing the stress-strain curves of each test specimen before hydrogen charging. [Figure 10] Scanning electron micrographs showing the fracture surfaces of each specimen before hydrogen charging. [Figure 11] Graph showing the stress-strain curves of each test specimen after hydrogen charging. [Figure 12] Scanning electron micrographs showing the fracture surfaces of each test piece after hydrogen charging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The main features of the embodiments described below are listed below. Note that the technical elements described below are independent technical elements that exhibit technical usefulness alone or in various combinations, and are not limited to the combinations described in the claims at the time of filing.

[0013] In one embodiment of the present technology, the method may further include a solution heat treatment step of holding the layered shaped body at 885 to 915°C or 965 to 995°C for 10 minutes to 2 hours, and then quenching to room temperature, and an aging treatment step of holding the layered shaped body at 680 to 700°C for 16 hours or more, and then air-cooling to room temperature after the solution heat treatment step. The solution heat treatment step may be performed on the shaped layered shaped body, or may be performed on the layered shaped body that has been finish-processed. The aging treatment step may be performed at any timing after the solution heat treatment step. That is, the aging treatment step may be performed after the solution heat treatment step is performed on the shaped layered shaped body and the finish processing is performed.

[0014] In this configuration, the Vickers hardness of the layered molded body can be increased to 300 HV or more by the above-mentioned solution heat treatment and aging treatment. This ensures the strength of the high-strength parts to be manufactured. As a result, it is possible to increase the contact surface pressure between the high-strength parts to be manufactured (e.g., high-pressure hydrogen piping parts, etc.) and the target structure to be contacted or fastened, and the high-pressure hydrogen or liquefied hydrogen can be sealed and leakage of these can be suppressed.

[0015] In one embodiment of the present technology, the 3D additive manufacturing process may be either a powder bed fusion process or a directed energy deposition process.

[0016] In such a configuration, powder bed fusion can be selected when emphasis is placed on the geometrical accuracy of the product, while directed energy deposition can be selected when emphasis is placed on larger products or production speed.

[0017] In one embodiment of the present technology, the layered manufactured body after the aging treatment process may have a tensile strength of 950 MPa or more, a yield stress of 700 MPa or more, a breaking elongation of 23% or more, and a reduction in area of ​​50% or more.

[0018] In such a configuration, by finishing the additive manufacturing body, it is possible to obtain a high-strength part that has the same strength and hydrogen embrittlement resistance as conventional steel materials (e.g., melt-cast bar material).

[0019] In one embodiment of the present technology, after the aging treatment process, the layered product is subjected to hydrogen charging by holding it in a 100 MPa hydrogen atmosphere at 270°C for 200 hours, and the layered product may have a breaking elongation of 0.8 times or more and a reduction in area of ​​0.5 times or more compared to the layered product before the hydrogen charging.

[0020] In such a structure, even when a high-strength part is used in an environment where hydrogen permeates, hydrogen embrittlement fracture or delayed fracture is unlikely to occur.

[0021] In one embodiment of the present technology, the additive manufacturing body may have a through hole penetrating in an axial direction thereof, and may have a cylindrical shape in which a plurality of concentric parts having different diameters are connected along the axial direction.

[0022] In one embodiment of the present technology, the high-strength part may be a piping fastener connecting two pipes, and the finishing process may include a step of forming a threaded portion in the two axially spaced portions.

[0023] Hereinafter, the manufacturing method of the high-strength hydrogen piping component disclosed in this specification (hereinafter referred to as the present manufacturing method) will be described with reference to the drawings. The present manufacturing method includes a layered molding manufacturing process, a solution heat treatment process, an aging treatment process, and a high-strength hydrogen piping component manufacturing process. Note that the high-strength hydrogen piping component manufactured in the following description is only one example, and the present manufacturing method can be used to appropriately manufacture components having other shapes or components used for other purposes.

[0024] First, we will explain the additively molded body 10 produced by this manufacturing method, and the high-strength part 30 produced by this manufacturing method. In this manufacturing method, a piping fastener 30 shown in Fig. 3 is produced as the high-strength part 30. The piping fastener 30 is used when fastening together pipes through which water or oil flows.

[0025] As shown in FIG. 1, the layered object 10 produced by this manufacturing method has a first portion 12, a second portion 14, a third portion 16, a fourth portion 18, and a fifth portion 20. The portions 12 to 20 are concentrically connected. The length Ls of the layered object 10 in the direction along the axis A of the layered object 10 (hereinafter, the axial direction) is t The total length is 49.9 mm. For the sake of convenience, the left side of the drawing will be referred to as "upper" and the right side of the drawing as "lower".

[0026] The first portion 12 has a cylindrical shape with a diameter Ds1 of 12.6 mm. The length Ls1 of the first portion 12 in the axial direction is 10.35 mm.

[0027] The second portion 14 is connected to the lower end of the first portion 12. The second portion 14 has an inclined portion 14a and a body portion 14b. The inclined portion 14a has a conical shape that expands in diameter downward, and is connected to the lower end of the first portion 12. The inclined portion 14a is inclined at 45 degrees with respect to the axis A. The length Ls of the inclined portion 14a in the axial direction is 21 The diameter of the upper end of the inclined portion 14a is approximately equal to the diameter of the first portion 12. The body portion 14b has a regular hexagonal prism shape and is connected to the lower end of the inclined portion 14a. The length Ls of the body portion 14b in the axial direction is approximately equal to the diameter of the first portion 12. 22 2, when the layered object 10 is viewed from above, the length d1 between two opposing sides of the hexagon constituting the body 14b is 19 mm, and the length d2 between two opposing vertices across the axis is 21.5 mm.

[0028] The third portion 16 is connected to the lower end of the second portion 14. The third portion 16 has a body portion 16a and an inclined portion 16b. The body portion 16a has a cylindrical shape and is connected to the lower end of the second portion 14 (body portion 14b). The diameter Ds3 of the body portion 16a is 13.45 mm. The inclined portion 16b has a conical shape that narrows downward and is connected to the lower end of the body portion 16a. The inclined portion 16b is inclined at 60 degrees with respect to the axis A. The length Ls3 of the entire third portion 16 in the axial direction is 12.6 mm.

[0029] The fourth portion 18 is connected to the lower end of the third portion 16. The fourth portion 18 has a body portion 18a and an inclined portion 18b. The body portion 18a has a cylindrical shape and is connected to the lower end of the third portion 16 (inclined portion 16b). The diameter Ds4 of the body portion 18a is 9.357 mm. The diameter of the body portion 18a is approximately equal to the diameter of the lower end of the inclined portion 16b of the third portion 16. The length Ls of the body portion 18a in the axial direction 41 The length Ls of the inclined portion 18b in the axial direction is 6.208 mm. The inclined portion 18b has a conical shape that tapers downward, and is connected to the lower end of the body portion 18a. The diameter of the upper end of the inclined portion 18b is slightly smaller than the diameter of the body portion 18a. The inclined portion 18b is inclined at 19 degrees with respect to the axis A. The length Ls of the inclined portion 18b in the axial direction is 6.208 mm. 42 is 2.092 mm.

[0030] The fifth portion 20 is connected to the lower end of the fourth portion 18. The fifth portion 20 has a cylindrical shape with a diameter Ds5 of 6.985 mm. The diameter of the fifth portion 20 is approximately equal to the diameter of the lower end of the inclined portion 18b of the fourth portion 18. The length Ls5 of the fifth portion 20 in the axial direction is 5.65 mm. As is clear from the above description, the diameters Ds1, Ds3, Ds4, and Ds5 of the first portion 12, the third portion 16, the fourth portion 18, and the fifth portion 20 are different from each other, and the axial lengths Ls1, Ls2 (=Ls 21 +Ls 22 ), Ls3, Ls4 (=Ls 41 +Ls 42 ), and Ls5 are also different.

[0031] As shown in FIG. 3, each of the portions 12 to 20 has a through hole 22 that passes through the portion 12 to 20 in the axial direction. The through hole 22 has a circular shape in a top view (a cross section perpendicular to the axis). The through hole 22 has a uniform diameter Ds in (2.65 mm) and gradually expands in diameter midway through first portion 12. The expanding portion of through hole 22 is inclined at 30 degrees with respect to axis A. The diameter of through hole 22 at the upper end of first portion 12 is 7.28 mm.

[0032] The volume density of the layered product 10 is 99.9% or more. The volume density is, for example, 99.92% or more, such as 99.93% or more, such as 99.94% or more, such as 99.95% or more, such as 99.96% or more, such as 99.97% or more, such as 99.98% or more, or such as 99.99% or more.

[0033] Next, a high-strength part (i.e., a pipe fastener 30) manufactured by this manufacturing method will be described. As shown in FIG. 4, the pipe fastener 30 has a first portion 32, a second portion 34, a third portion 36, a fourth portion 38, and a fifth portion 40. The portions 32 to 40 are concentrically connected. The length Lf of the pipe fastener 30 in the axial direction is t (Total length) is 48.1mm.

[0034] The first portion 32 has a cylindrical shape. The first portion 32 has a threaded portion 32a and a constricted portion 32b connected to the lower end of the threaded portion 32a. A male thread is formed around the periphery of the threaded portion 32a. The effective depth of the threaded portion 32a is 12 mm. A chamfered portion 32c is formed at the upper end of the threaded portion 32a. The constricted portion 32b has a smaller diameter than the threaded portion 32a. The length Lf1 of the first portion 32 in the axial direction (Ls1 + Ls 21 (corresponding to ) is 14.3 mm.

[0035] The second portion 34 is connected to the lower end of the first portion 32. The second portion 34 has a regular hexagonal cylindrical shape. The length Lf2 of the second portion 34 in the axial direction (Ls 22 5, when pipe fastener 30 is viewed from above, length d3 between two opposing sides of the hexagon constituting second portion 34 is 19 mm, and length d4 between two opposing vertices across the axis is 21.5 mm.

[0036] The third portion 36 is connected to the lower end of the second portion 34. The third portion 36 has a base portion 36a, a threaded portion 36b, and a constricted portion 36c connecting the base portion 36a and the threaded portion 36b. The base portion 36a is connected to the lower end of the second portion 34. The length of the base portion 36a in the axial direction is 2.1 mm. The threaded portion 36b is connected to the lower end of the base portion 36a via the constricted portion 36c. A male thread is formed around the periphery of the threaded portion 36b. The effective depth of the threaded portion 36b is 7 mm. The base portion 36a, the threaded portion 36b, and the constricted portion 36c all have a cylindrical shape, and the diameter of the constricted portion 36c is smaller than the diameters of the base portion 36a and the threaded portion 36b. The length Lf3 (corresponding to Ls3) of the entire third portion 36 in the axial direction is 12.1 mm.

[0037] The fourth portion 38 is connected to the lower end of the third portion 36. The fourth portion 38 has a body portion 38a and an inclined portion 38b. The body portion 38a has a cylindrical shape and is connected to the lower end of the third portion 36 (threaded portion 36b). The diameter Df4 (corresponding to Ds4) of the body portion 38a is 8.79 mm. The length Lf of the body portion 38a in the axial direction is 8.79 mm. 41 (Ls 41 The length Lf of the inclined portion 38b in the axial direction is 6.4 mm. The inclined portion 38b has a conical shape that tapers downward, and is connected to the lower end of the body portion 38a. The diameter of the upper end of the inclined portion 38b is slightly smaller than the diameter of the body portion 38a. The inclined portion 38b is inclined at 19 degrees with respect to the axis A. The length Lf of the inclined portion 38b in the axial direction is 6.4 mm. 42 (Ls 42 (corresponding to ) is 1.95 mm.

[0038] The fifth portion 40 is connected to the lower end of the fourth portion 38. The fifth portion 40 has a cylindrical shape with a diameter Df5 (corresponding to Ds5) of 6.4 mm. The diameter of the fifth portion 40 is approximately equal to the diameter of the lower end of the inclined portion 38b of the fourth portion 38. The length Lf5 (corresponding to Ls5) of the fifth portion 40 in the axial direction is 5.65 mm. As is clear from the above, the dimensions (Ls, Ds, d1, d2) of the layered object 10 are set slightly larger than the dimensions (Lf, Df, d3, d4) of the piping fastener 30. However, the dimensions (d1, d2) of the body 14b of the second portion 14 of the layered object 10 are set to be the same as the dimensions (d3, d4) of the second portion 34 of the piping fastener 30, since dimensional accuracy is not required. That is, the final shape is formed at the stage of molding the layered object 10.

[0039] As shown in Fig. 6, a through hole 42 is formed in each of the portions 32 to 40, penetrating the portion 32 to 40 in the axial direction. The through hole 42 has a circular shape in a top view. The through hole 42 has a uniform diameter Df in1 (3.2mm)(>Ds in =2.65 mm) and gradually expands in diameter from the middle of the first portion 32. The expanding portion of the through hole 42 is inclined at 30 degrees with respect to the axis A. The diameter Df of the through hole 42 at a point 0.9 mm below the upper end of the first portion 32 (i.e., the upper end of the male thread of the threaded portion 32a) is in2 is 6.5mm.

[0040] In this manufacturing method, after manufacturing the layered object 10 shown in Fig. 1, the layered object 10 is subjected to a solution heat treatment and an aging treatment, and then the layered object 10 is finish-processed to manufacture the piping fastener 30 shown in Fig. 4. Hereinafter, this manufacturing method will be specifically described.

[0041] (Layered modeling process) First, a three-dimensional additive manufacturing method using a metal 3D printer is used to manufacture an additive manufacturing body 10 from metal powder. The metal powder used for manufacturing contains, by weight, C: 0.010% to 0.025%, Si: 0.15% to 0.15%, Mn: 0.01% to 0.01%, S: 0.01% to 0.01%, Ni: 24% to 27%, Cr: 13.5% to 16%, Mo: 1% to 1.5%, V: 0.1% to 0.5%, Al: 0.35% to 0.35%, Ti: 1.90% to 2.35%, B: 0.0006% to 0.0020%, and the remainder is Fe and unavoidable impurities.

[0042] C: 0.010% or more and 0.025% or less If the C content exceeds 0.025%, in three-dimensional additive manufacturing, when the molten layer solidifies and when the layer laminated below the molten layer is heated again by the molten layer, it segregates at the grain boundaries of the additive manufacturing body, reducing the ductility and toughness of the additive manufacturing body and making it easier for microcracks to occur along the grain boundaries. On the other hand, if the C content is reduced to zero, it leads to grain coarsening in solution heat treatment and aging treatment, resulting in reduced fracture elongation and reduction in reduction in reduction in drawing. For these reasons and considering the values ​​that can be reduced industrially, including refining costs, the lower limit was set to 0.010%. Note that, when the C content is within the above range, it preferentially precipitates as TiC on the high temperature side during solidification of the molten layer, and also functions as a pin for grain growth.

[0043] Si:0.15% or less Silicon is used as a deoxidizer and is an element that improves the strength of the additive manufacturing body by solid solution strengthening. On the other hand, in 3D additive manufacturing, when the molten layer solidifies and when the layer laminated below the molten layer is heated again by the molten layer, silicon combines with Fe, Ni, Ti, and Mo to precipitate a low-melting eutectic compound (Laves phase) at the grain boundaries, causing liquation cracking or ductility dip cracking, i.e., microcracks, along the grain boundaries. Therefore, the silicon content was reduced to the extent that it is possible to reduce it industrially, including refining costs, and the upper limit was set at 0.15%.

[0044] Mn: 0.15% or less Mn is used as a deoxidizer, and is also an element that dissolves in austenite to stabilize it and ensure mechanical strength and toughness. However, if the Mn content exceeds 0.15%, it tends to promote microcracks at grain boundaries during three-dimensional additive manufacturing, so it has been reduced to the extent that is generally industrially feasible, including refining costs, and the upper limit has been set at 0.15%.

[0045] P:0.01% or less P is a low melting point inclusion, and even a very small amount of P promotes microcracks at grain boundaries during 3D additive manufacturing, so it is desirable to reduce it as much as possible. On the other hand, excessive refining leads to increased costs, so it is reduced to the extent possible in general industry, and the P content is set at 0.01% or less.

[0046] S: 0.01% or less S is a low-melting-point inclusion, and even a very small amount of it can promote microcracks at grain boundaries during 3D additive manufacturing, so it is desirable to reduce it as much as possible. On the other hand, excessive refining leads to increased costs, so it is reduced to the extent possible in general industry, with the S content set at 0.01% or less.

[0047] Ni: 24% or more and 27% or less Ni is a major element that stabilizes austenite and provides excellent resistance to hydrogen embrittlement, and it is necessary to add a sufficient amount to ensure a nickel equivalent (Hirayama formula) of 28.5 or more, which is an austenite stabilization index. On the other hand, excessive content leads to increased costs and reduced recyclability. In consideration of these, the Ni content is set at 24% or more and 27% or less.

[0048] Cr:13.5% or more and 16% or less Cr is a key element for improving corrosion resistance and imparting excellent resistance to hydrogen embrittlement. However, excessive inclusion of Cr leads to increased costs, so the Cr content is set at 13.5% to 16%.

[0049] Mo: 1% or more and 1.5% or less Mo is an element that strengthens the solid solution of austenite and provides excellent resistance to hydrogen embrittlement. However, excessive inclusion of Mo leads to increased costs, so the Mo content is set at 1% to 1.5%.

[0050] V: 0.10% or more and 0.50% or less V is an element that preferentially precipitates as carbide at the high temperature stage during solidification and contributes to preventing grain coarsening. However, excessive inclusion of V leads to increased costs, so the V content is set at 0.10% to 0.50%.

[0051] Al: 0.35% or less Al is used as a deoxidizer, and is an element that precipitates the γ' phase (gamma prime phase, Ni3(Al,Ti)) during aging treatment, resulting in age hardening and increased strength. The lower the Ti / Al ratio, that is, the higher the Al content, the more stable the γ' phase becomes, but at the same time, the longer the heat treatment time required for age hardening becomes, so industrially, the Al content is set at 0.35% or less so that peak hardness is achieved in 3-20 hours.

[0052] Ti: 1.90% or more and 2.35% or less Ti is an element that precipitates the γ' phase (gamma prime phase, Ni3(Al,Ti)) during aging treatment, resulting in age hardening and increased strength. In addition, it is an element that preferentially precipitates as carbides at the high temperature stage of solidification, contributing to preventing grain coarsening. However, excessive inclusion of Ti leads to increased costs, so the Ti content is set at 1.90% to 2.35%.

[0053] B: 0.0006% or more and 0.0020% or less In conventional smelted materials, i.e., materials that have been cast and hot rolled, B is an element that increases the strength of the grain boundaries and improves the breaking elongation and reduction of area at room temperature, as well as creep resistance at high temperatures. On the other hand, in three-dimensional additive manufacturing, when the molten layer solidifies and when the layer laminated below the molten layer is heated again by the molten layer, B combines with other alloy elements to precipitate low-melting eutectic compounds at the grain boundaries, causing liquation cracks, i.e., microcracks, along the grain boundaries. Therefore, it is desirable to reduce B as much as possible without sacrificing the breaking elongation and reduction of area at room temperature, and the B content is set to 0.0006% or more and 0.0020% or less.

[0054] The above metal powder has a nickel equivalent, Ni, defined by the following formula: eq (Hirayama formula) is 28.5 or more. Ni eq =12.6×[C%]+0.35×[Si%]+1.05[Mn%]+[Ni%]+0.65[Cr%]+0.98[Mo%] By using a metal powder having the above-mentioned nickel equivalent, it is possible to impart high strength and excellent hydrogen embrittlement resistance to the manufactured high-strength hydrogen piping component 30. The particle size of the metal powder is not particularly limited, but is, for example, 10 μm to 100 μm. The use of a metal powder having such a particle size can contribute to improving the volume density of the high-strength hydrogen piping component that is three-dimensionally additively manufactured.

[0055] In this manufacturing method, the three-dimensional additive manufacturing method is selected from either Powder Bed Fusion (PBF) or Directed Energy Deposition (DED). In PBF, a laser or electron beam is irradiated onto metal powder spread on a modeling plate. This melts the metal powder, and the area where the molten metal powder solidifies and bonds becomes the modeled object. When modeling of one layer is completed, metal powder for forming the next layer is again spread on the modeling plate. This process is repeated in the stacking direction to form the additive manufactured object 10 shown in FIG. 1.

[0056] In DED, a laser is irradiated onto a modeling plate, and metal powder is sprayed onto the laser irradiated area. This melts the metal powder at the irradiated area. In DED, the metal powder is sprayed while the laser irradiated area is moved on the modeling plate, so that the melting and solidification of the metal powder proceeds repeatedly. This process is repeated in the stacking direction to form the additive manufacturing object 10 shown in FIG. 1.

[0057] In any of the above methods, the layer pitch (thickness of one layer) can be, for example, 10 to 100 μm. However, the layer pitch is not limited to this and may be adjusted appropriately depending on the particle size of the metal powder used. In this manufacturing method, as shown in FIG. 7, a plurality of layered objects 10 are formed on a modeling plate 50. This makes it possible to reduce modeling costs. As is clear from FIG. 7, the layered objects 10 are formed in sequence from the first portion 12 side toward the fifth portion 20 side.

[0058] (Solution heat treatment process) Next, the layered product 10 is subjected to a solution heat treatment process. The solution heat treatment process is mainly carried out to remove residual stress in the layered product 10 caused by shaping and to dissolve compounds precipitated during shaping. In the solution heat treatment process, the layered product 10 is held at 885 to 915°C or 965 to 995°C for 10 minutes to 2 hours, and then rapidly cooled to room temperature. The holding time in the above temperature range can be appropriately adjusted depending on the required purpose, such as when it is desired to refine the crystal grains or when it is desired to completely dissolve the shaped product.

[0059] (Aging treatment process) Next, an aging treatment process is performed on the additive manufacturing body 10. The aging treatment process is performed mainly to precipitate an intermetallic compound called γ' phase (gamma prime phase, Ni3(Al,Ti)) to improve the hardness of the additive manufacturing body 10. In the aging treatment process, the additive manufacturing body 10 is held at 680 to 700°C for 16 hours or more, and then air-cooled to room temperature.

[0060] (Finishing process) Next, the layered object 10 is subjected to a finishing process. Examples of the finishing process include removal processes such as cutting and grinding, and surface treatments for modifying the surface of the component. In this manufacturing method, the layered object 10 is finished in the axial direction thereof, except for the side surface of the hexagonal column of the body 14b, to manufacture the piping fastener 30 shown in FIG. 4 from the layered object 10.

[0061] As described above, in this manufacturing method, the piping fastener 30 is manufactured by finishing the layered object 10 manufactured by the three-dimensional additive manufacturing method. Therefore, by manufacturing the layered object 10 approximating the shape of the piping fastener 30 to be manufactured by the three-dimensional additive manufacturing method, the finishing processing allowance can be reduced. Specifically, in this manufacturing method, the cutting allowance in the finishing process can be reduced to about 1 mm. Therefore, compared to the conventional case of manufacturing the target part from a steel material (e.g., a molten bar material), the process of finishing processing such as cutting can be significantly reduced.

[0062] Furthermore, in the present manufacturing method, even when a material with a high nickel equivalent that is difficult to process is used, the effect on the processability of the material is reduced, which reduces the effect on the cutting process that is highly dependent on the skill of the worker, and improves the precision of the manufactured pipe fastener 30.

[0063] In the above-mentioned manufacturing method, a method for manufacturing the piping fastener 30 has been described. However, the technology disclosed in this specification may be applied when manufacturing other parts. Specifically, for example, it may be used when manufacturing metal parts (bolts, nuts, etc.) used in a hydrogen intrusion environment.

[0064] In the above manufacturing method, the shaped layered product 10 was subjected to solution heat treatment and aging treatment in order, and then the finish processing was performed. Since the finish processing is performed in the final step, the shape and surface roughness quality of the manufactured pipe fastener 30 can be easily controlled. However, in the present manufacturing method, for example, the shaped layered product 10 may be subjected to solution heat treatment and aging treatment in order after the finish processing. In this case, the layered product 10 is first subjected to the finish processing, so that the quality of the reference surface for the finish processing can be controlled by the conditions of the layered product manufacturing. Also, for example, the shaped layered product 10 may be subjected to solution heat treatment, and then the finish processing and aging treatment in order. In this case, the relatively soft layered product 10 after the solution heat treatment is subjected to the finish processing (cutting, surface treatment, etc.), so that the workability of the finish processing can be improved. In this way, in the present manufacturing method, the order of each process may be appropriately changed depending on the shape of the manufactured part and the required quality.

[0065] Specific examples of the technology disclosed in this specification will be described below, although the disclosure of this specification is not limited to the following specific examples.

[0066] <Production of a molded object for evaluating volume density> First, a metal powder having composition A shown in Table 1 was prepared. The particle size of the metal powder was 15 to 53 μm. Then, in order to examine the volume density of a three-dimensional additive manufacturing object by powder bed fusion (PBF) using this powder, a 10 mm square cube was manufactured for preliminary evaluation under multiple laser irradiation conditions. As a result, it was found that the energy density by laser irradiation was 60 J / mm 3 It was found that the volume density reached 99.9% or more when the above conditions were met. The volume density was measured by mirror-polishing the cross section of the molded body in the Z-axis direction for 3 minutes and then performing image analysis.

[0067] [Table 1]

[0068] <Preparation of test pieces in Examples 1 to 3> (Fabrication of additively manufactured objects and processing them into SSRT test pieces) Using the same metal powder (composition A, particle size 15 to 53 μm) as the metal powder used for the above evaluation model, a Φ18L80 round bar was additively manufactured by powder bed fusion (PBF) three-dimensional additive manufacturing under the above laser irradiation conditions to become the base material for the SSRT test specimen. The volume density of this base material Φ18L80 round bar was 99.9% or more. Next, this model was subjected to solution heat treatment and aging treatment described in detail below, and then machined to complete the SSRT test specimen 100 shown in FIG. 8.

[0069] (Solution heat treatment) The additively molded body of the Φ18L80 round bar of raw material was subjected to solution heat treatment as specified in JIS G4311. Specifically, the additively molded body of the Φ18L80 round bar of raw material was held at 980°C for 1 hour and then rapidly cooled to room temperature, thereby carrying out solution heat treatment.

[0070] (Aging process) After the solution heat treatment, the laminated body of the Φ18L80 round bar of the raw material was held at 690°C for 20 hours, and then air-cooled to room temperature for aging treatment. Prior to setting the treatment temperature conditions, samples 1 to 4 of 10 mm square cubes, which were three-dimensionally laminated and solution-treated under the same conditions as the Φ18L80 round bar, were compared and evaluated for aging treatment at 680 to 740°C. The soaking time in the aging treatment was unified to 20 hours so that the maximum hardness could be obtained. The evaluation was performed based on the Vickers hardness HV10kg at five points in the Z-axis cross section of the cube, and the presence or absence of microcracks (hereinafter referred to as indentation cracks) generated from the corners of the square indentation added to the test surface in the Vickers hardness test. The results are shown in Table 2. Regarding the Vickers hardness in Table 2, A indicates the value at the center of the Z-axis cross section, and B to E indicate the values ​​near the four corners of the Z-axis cross section. The values ​​at the locations where dent cracks occurred are underlined. The dent crack frequency indicates the number of dent cracks that occurred in the above five locations A to E.

[0071] [Table 2]

[0072] As shown in Table 2, samples 3 and 4, which were aged at 720°C and 740°C, had Vickers hardnesses of 343 to 363HV, but showed impression cracks. On the other hand, samples 1 and 2, which were aged at 680°C and 700°C, had high Vickers hardnesses (342 to 360HV) and showed no impression cracks. In other words, it was found that aging at 700°C or less suppressed embrittlement and provided high strength.

[0073] (machined finish) After the aging treatment, the SSRT test piece 100 shown in FIG. 8 was produced by cutting and finishing. As shown in FIG. 8, the SSRT test piece 100 has a shaft portion 110 and fixing portions 120 provided at both ends of the shaft portion 110. Each fixing portion 120 is provided at each end of the shaft portion 110 via a transition portion 130. The shaft portion 110 has a cylindrical shape with a diameter Dt1 of about 6 mm and an axial length Lt1 of about 30 mm. Each transition portion 130 has a tapered shape and connects the shaft portion 110 and each fixing portion 120. Each fixing portion 120 has a cylindrical shape with a diameter Dt2 of about 18 mm and an axial length Lt2 of about 18 mm. The shaft portion 110, the fixing portion 120, and the transition portion 130 were mirror-polished. The shaft portion 110 was cut and finished by the following procedure. First, the cutting was performed with a depth of cut of 0.1 mm from a diameter of 7.0 mm to a diameter of 6.2 mm. Next, the cutting was performed with a depth of cut of 0.05 mm from a diameter of 6.2 mm to a diameter of 6.1 mm. Next, the cutting was performed to a diameter of 6.07 mm. The remaining 70 μm was polished off with emery paper and buffing. The mirror-finished part was observed all around with a 40x magnifying glass to confirm that there were no scratches in the circumferential direction. It was also confirmed that the axial runout of the shaft part 110 and both fixing parts 120 was 0.05 mm or less.

[0074] The test pieces of Examples 2 and 3 were also prepared by the same procedure as the test piece of Example 1 using the same metal powder as that of Example 1.

[0075] <Preparation of test pieces in Examples 4 to 6> For Examples 4 to 6, the SSRT test piece 100, which was made of an additive manufacturing body produced by the same procedure as in Example 1, was subjected to the following forced hydrogen charging to prepare a test piece. First, the SSRT test piece 100 was degreased with acetone before hydrogen charging in order to remove oil that may have adhered or remained during the manufacturing process. Thereafter, the SSRT test piece 100 was held at 270°C for 200 hours in a hydrogen atmosphere of 100 MPa (1000 atm), thereby carrying out hydrogen charging on the SSRT test piece 100. After hydrogen charging, the SSRT test piece 100 was stored in liquid nitrogen to prevent hydrogen release. The hydrogen concentration of the test piece after hydrogen charging was 77 ppm.

[0076] <Preparation of test pieces for Comparative Examples 1 to 3> The test pieces of Comparative Examples 1 to 3 were produced in the same manner as the test piece of Example 1, except that a metal powder having composition B in Table 1 was used.

[0077] <Preparation of test pieces for Comparative Examples 4 to 6> For Comparative Examples 4 to 6, the SSRT test piece 100 was made from an additive manufacturing body produced by the same procedure as in Comparative Example 1, and hydrogen was charged under the same conditions as in Example 4 and the like to prepare the test piece.

[0078] <Preparation of test pieces for controls 1 to 3> For Control 1, first, a commercially available ingot bar material (SUH660) was processed into a shape similar to that of the SSRT test piece 100 using the additive manufacturing body shown in FIG. 8 as a material. Next, the processed ingot bar material was subjected to solution heat treatment and aging treatment. The solution heat treatment temperature was 980 to 990 ° C, and the aging treatment was held at 720 ° C for 16 hours and then air-cooled to room temperature. The ingot bar material subjected to the aging treatment was used as the test piece for Control 1. The test pieces for Controls 2 and 3 were also prepared using the same ingot bar material and in the same procedure as the test piece for Control 1.

[0079] <Preparation of test pieces for Controls 4 to 6> For Controls 4 to 6, the test pieces were prepared by subjecting the ingot bar material processed in the same manner as in Control 1 to hydrogen charging under the same conditions as in Example 4 and the like.

[0080] (SSRT test) For each test piece, a crosshead speed of 1.5 μm / sec (strain rate 5 × 10 -5 The slow strain rate tensile test (SSRT) was carried out at a strain rate of 100 / sec to measure the tensile strength, yield stress, elongation at break, and reduction in area. The measurement results are shown in Table 3.

[0081] [Table 3]

[0082] FIG. 9 is a stress-strain curve showing the results of the SSRT test performed on each test piece of Example 1, Comparative Example 1, and Control 1. That is, FIG. 9 shows the test results of each test piece before hydrogen charging. As shown in Table 3 and FIG. 9, the tensile strength and yield stress of all test pieces were equivalent. Meanwhile, the fracture elongation of the test piece of the comparative example was 15-19%, whereas the test piece of the example was 25-26%, which is a significantly high value. This is a value equivalent to the value (26-27%) of the test piece (control) processed from the conventional ingot bar material, and it can be seen that the test pieces of Examples 1-3 have high ductility despite their high strength. In addition, the reduction of area of ​​the test piece of the comparative example was 20-24%, whereas the test piece of the example was 52-57%, which is a significantly high value. This is the same value as the value (52 to 53%) of the test piece (control) processed from the conventional molten bar material, and it can be seen that the test pieces of Examples 1 to 3 have high ductility. This is thought to be because the microcracks of the test pieces of the Examples are reduced to an extremely low level by adjusting the component composition of the metal powder and various processing conditions after molding. Microcracks promote crack generation and propagation due to stress in the SSRT test. That is, it is thought that the test pieces of the Examples, which have almost no microcracks, exhibit high fracture elongation and reduction in area because cracks are unlikely to occur and propagate. Furthermore, in the test pieces of the Examples, by adjusting the component composition of the metal powder, low-melting eutectic compounds are unlikely to precipitate at the grain boundaries. The eutectic compounds are very hard and brittle, so they can contribute to crack generation and propagation due to stress during the SSRT test. Therefore, it is thought that the strength and ductility are improved in the Examples, which use metal powders having a component composition that makes it difficult for such eutectic compounds to precipitate.

[0083] Fig. 10 shows scanning electron microscope photographs of the fracture surfaces after the SSRT test of each of the test pieces of Example 1, Comparative Example 1, and Control 1. Fig. 10(a) shows the fracture surface of the test piece of Example 1, Fig. 10(b) shows the fracture surface of the test piece of Comparative Example 1, and Fig. 10(c) shows the fracture surface of the test piece of Control 1. The fracture surfaces of the test pieces of Example 1 and Control 1 were so-called cup-and-cone types, while the fracture surface of the test piece of Comparative Example 1 was perpendicular to the stress acting direction (so-called perpendicular fracture).

[0084] FIG. 11 is a stress-strain curve showing the results of the SSRT test performed on each test piece of Example 4, Comparative Example 4, and Control 4. That is, FIG. 11 shows the test results of each test piece after hydrogen charging. As shown in Table 3 and FIG. 11, the tensile strength and yield stress of all test pieces were equivalent. On the other hand, the fracture elongation of the test piece of the comparative example was 10 to 12%, while the test piece of the example was 22 to 23%, which is a significantly high value. This is a value equivalent to the value (22%) of the test piece (control) processed from the conventional ingot bar material, and it can be seen that the test piece of the example has high ductility even after hydrogen charging. In addition, the reduction in area of ​​the test piece of the comparative example was 14 to 16%, while the test piece of the example was 29 to 33%, which is a significantly high value. This is a value equivalent to the value (32%) of the test piece (control) processed from the conventional ingot bar material, and it can be seen that the test piece of the example has high ductility even after hydrogen charging.

[0085] Fig. 12 shows scanning electron microscope photographs of the fracture surfaces after the SSRT test of each of the test pieces of Example 4, Comparative Example 4, and Control 4. Fig. 12(a) shows the fracture surface of the test piece of Example 4, Fig. 12(b) shows the fracture surface of the test piece of Comparative Example 4, and Fig. 12(c) shows the fracture surface of the test piece of Control 4. As with the fracture surface before hydrogen charging (Fig. 10), the fracture surfaces of the test pieces of Example 4 and Control 4 were cup-and-cone shaped, and the fracture surface of the test piece of Comparative Example 4 was perpendicular to the stress acting direction.

[0086] 9 and 11, the ratio of fracture elongation (relative fracture elongation) and the ratio of reduction in area (relative reduction in area) of each test piece before and after hydrogen charging were compared. The relative fracture elongation was 0.53 in the comparative example, whereas the Example had a significantly higher result of 0.92. The relative reduction in area was also 0.58 in the comparative example, whereas the Example had a higher result of 0.63. That is, it was found that the Example had superior hydrogen embrittlement resistance compared to the comparative example. This result is comparable to the relative fracture elongation (0.85) and relative reduction in area (0.62) of the control test piece. It is believed that such a result was obtained because the hydrogen-charged test piece caused the cracks to propagate more sensitively due to microcracks. As described above, the test piece of the Example had very few microcracks. Therefore, it is believed that the Example showed a small degree of hydrogen embrittlement and a high relative fracture elongation and relative reduction in area even after hydrogen charging. In this way, it was confirmed that by adjusting the component composition of the metal powder and the aging treatment conditions, etc., it is possible to manufacture high-strength parts that have high strength and excellent resistance to hydrogen embrittlement, even when using three-dimensional additive manufacturing.

[0087] In addition, both of the composition A and the composition B shown in Table 1 have compositions within the range of the composition of SUH660 defined in JIS G4311. However, as is clear from the above explanation, it has been confirmed that by adjusting the composition to a specific value within the range, it is possible to impart high strength and excellent hydrogen embrittlement resistance to the additive manufacturing body.

[0088] Although specific examples of the present invention have been described above in detail, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and variations of the specific examples exemplified above. The technical elements described in this specification or drawings exhibit technical utility alone or in various combinations, and are not limited to the combinations described in the claims at the time of filing. In addition, the technology exemplified in this specification or drawings achieves multiple objectives simultaneously, and achieving one of the objectives itself has technical utility. [Explanation of symbols]

[0089] 10: additively manufactured body, 12: first part, 14: second part, 14a: inclined portion, 14b: body part, 16: third part, 16a: body part, 16b: inclined portion, 18: fourth part, 18a: body part, 18b: inclined portion, 20: fifth part, 22: through hole, 30: piping fastener, 32: first part, 32a: threaded portion, 32b: constricted portion, 32c: chamfered portion, 34: second part, 36: third part, 36a: base part, 36b: threaded portion, 36c: constricted portion, 38: fourth part, 38a: body part, 38b: inclined portion, 40: fifth part, 42: through hole, 50: modeling plate

Claims

1. A method for manufacturing a high-strength part having excellent hydrogen embrittlement resistance, comprising the steps of: In weight percent, C: 0.010% or more and 0.025% or less, Si: 0.15% or less, Mn: 0.15% or less, P: 0.01% or less, S: 0.01% or less, Ni: 24% or more and 27% or less, Cr: 13.5% or more and 16% or less, Mo: 1% or more and 1.5% or less, V: 0.10% or more and 0.50% or less, Al: 0.35% or less, Ti: 1.90% or more and 2.35% or less, B: 0.0006% or more and 0.0020% or less, The remainder is composed of Fe and unavoidable impurities. 3 forming an additive manufacturing object having a volume density of 99.9% or more by the above-mentioned three-dimensional additive manufacturing method using a laser or an electron beam; and producing a high-strength part by finishing the additive manufactured body.

2. a solution heat treatment step of holding the layered product at 885 to 915°C or 965 to 995°C for 10 minutes to 2 hours, and then quenching the product to room temperature; The manufacturing method according to claim 1, further comprising an aging treatment step of holding the layered product at 680 to 700 ° C. for 16 hours or more after the solution heat treatment step, and then air-cooling the layered product to room temperature.

3. The method of claim 1 , wherein the three-dimensional additive manufacturing method is either a powder bed fusion method or a directed energy deposition method.

4. The manufacturing method according to claim 2, wherein the layered product after the aging treatment step has a tensile strength of 950 MPa or more, a yield stress of 700 MPa or more, a breaking elongation of 23% or more, and a reduction in area of ​​50% or more.

5. The manufacturing method according to claim 4, wherein the layered body after the aging treatment process is subjected to hydrogen charging by holding the layered body in a 100 MPa hydrogen atmosphere at 270°C for 200 hours has a breaking elongation of 0.8 times or more and a reduction in area of ​​0.5 times or more compared to the layered body before the hydrogen charging.

6. The manufacturing method according to any one of claims 1 to 5, wherein the layered object has a through hole penetrating in an axial direction, which is a direction along the axis of the layered object, and has a cylindrical shape in which a plurality of concentric parts having different diameters are connected along the axial direction.

7. the high-strength part is a pipe fastener for connecting two pipes, The method according to claim 6 , wherein the finishing process includes forming threads in the two axially spaced apart portions.

Citation Information

Patent Citations

  • Stainless steel powder for molding

    JP2019119913A

  • Metal powder

    JP2021181591A

  • Metal powder bonded body manufactured by additive manufacturing and having excellent hydrogen embrittlement resistance

    US20180015540A1